2018
DOI: 10.11110/kjpt.2018.48.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Floristic study of Aphaedo Island in Shinan-gun, Jeollanam-do, Korea

Abstract: We investigated vascular plants of Aphaedo Island in Shinan-gun, Jeollanam-do, Korea. By referring to voucher specimens collected over the course of 28 days from May of 2011 to March of 2016, a total of 451 taxa were identified and grouped into 102 families, 294 genera, 413 species, 6 subspecies, 30 varieties, and 2 forms, of which 9 taxa were classified as endangered or rare, including Albizia kalkora, Salomonia oblongifolia, and Centranthera cochinchinensis var. lutea. A total of 59 taxa were identified as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Thus, realistic removal and management of this species are difficult and showed no results so far (Ryu et al, 2017). From the discovery of H. radicata in Chungcheong and Jeolla, it shows that diffusion and settlement have already occurred inland (Hyun et al, 2018). Therefore, the case of H. radicata shows that there is a limitation in the existing management methods for general harmful species.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, realistic removal and management of this species are difficult and showed no results so far (Ryu et al, 2017). From the discovery of H. radicata in Chungcheong and Jeolla, it shows that diffusion and settlement have already occurred inland (Hyun et al, 2018). Therefore, the case of H. radicata shows that there is a limitation in the existing management methods for general harmful species.…”
Section: Introductionmentioning
confidence: 99%
“…Halla National Reserve. Furthermore, the discovery of H. radicata in Chungcheong and Jeolla shows that dispersal and settlement of this invasive plant species have already occurred in inland Korea ( Hyun et al., 2018 ), which could be accelerated by global climate change. Park (2022) also reported that the expansion of H. radicata was significantly influenced by development projects, such as the construction of residential areas and transportation systems.…”
Section: Discussionmentioning
confidence: 99%